2016
DOI: 10.5370/jeet.2016.11.5.1332
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Charge Accumulation and Decay on Silicone Rubber/SiO2Nanocomposite Surface

Abstract: -The accumulation and decay of surface charge on silicone rubber (SiR)/SiO 2 nanocomposites under a unipolar corona discharge field was investigated. The effect of the weight ratio of SiO 2 nanoparticles from 0.1 to 0.7 wt.% was studied. Attenuated total reflection infrared spectra of the SiR/SiO 2 nanocomposites indicated that the SiO 2 nanoparticles chemically and physically interacted with the SiR matrix. This facilitated the SiR chains in restricting the injection of surface charge into the bulk nanocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A substantial number of researches have been demonstrated that the surface modification can accelerate the surface charge dissipation and improve the insulation properties of epoxy resin [6][7][8][9][10]. The surface modification can be achieved by many chemical or physical methods, including direct fluorination [11][12][13], nanoparticles doping [14,15], electron beam irradiation [16,17], heat treatment [18] and Cr 2 O 3 coating treatment [7], etc. However, above methods are still difficult to be widely used in industrial applications due to expensive equipment, complex processes or exhaust gas emission.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of researches have been demonstrated that the surface modification can accelerate the surface charge dissipation and improve the insulation properties of epoxy resin [6][7][8][9][10]. The surface modification can be achieved by many chemical or physical methods, including direct fluorination [11][12][13], nanoparticles doping [14,15], electron beam irradiation [16,17], heat treatment [18] and Cr 2 O 3 coating treatment [7], etc. However, above methods are still difficult to be widely used in industrial applications due to expensive equipment, complex processes or exhaust gas emission.…”
Section: Introductionmentioning
confidence: 99%